Sustainability of the polymer SH reinforced recycled granite residual soil: properties, physicochemical mechanism, and applications - Yuan, Bingxiang; Chen, Weijie; Li, Zihao; Zhao, Jin; Luo, Qingzi; Chen, Wenwu; Chen, Tianying (Journal of soils and sediments, 2023)
Purpose More than 2 billion tons of construction waste soil are generated every year in China, leading to waste and degradation of land resources. This study aims to develop a reinforcement technology for granite residual soil, the common type of construction waste in China, evaluate the reinforcement properties, and investigate the mechanism. Method In this study, the polymer SH, glass fiber, and granite residual soils were mechanically mixed to prepare specimens for impact resistance tests. Additionally, the specimens obtained were characterized using a combination of techniques including X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). Results The low-velocity impact test showed that the impact resistance of granite residual soil is highly related to the content of SH. When the content reaches 3.5%, the impact resistance is the best. Results of characterization revealed that kaolinite plays an important role in the reinforcement system, which can be summarized into the following: (1) the hydrophobic group (C–C) on the SH molecular chain is bridged on the surface of kaolinite, transforming kaolinite from hydrophilic to hydrophobic; thus, the disintegration characteristic of GRS in water was moderated. (2) The pores between kaolinite are also filled by SH molecular chains. (3) In particular, the frictional engagement of kaolinite and glass fiber also enables the tensile strength of glass fiber to be exerted. Conclusion These findings provide possibilities for the effective recycling of granite residual soil on a vast scale and the sustainable development of construction waste soils.